1999
DOI: 10.1523/jneurosci.19-22-09953.1999
|View full text |Cite
|
Sign up to set email alerts
|

Entorhinal Cortex Lesion in Adult Rats Induces the Expression of the Neuronal Chondroitin Sulfate Proteoglycan Neurocan in Reactive Astrocytes

Abstract: The chondroitin sulfate proteoglycan neurocan is a major component of brain extracellular matrix during development. Neurocan is primarily synthesized by neurons and has the ability to interact with cell adhesion molecules involved in the regulation of cell migration and axonal growth. Within the first weeks postnatally, neurocan expression is strongly downregulated. To test whether neurocan is reexpressed in areas of axonal growth (sprouting) after brain injury, the time course of neurocan expression was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
97
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 61 publications
(77 reference statements)
7
97
0
1
Order By: Relevance
“…Our results indicate that cultured astrocytes produce neurocan and that the SW injury induced substantial upregulation of neurocan mRNA, which is consistent with previous in vitro (30) and in vivo (6,29,31) observations. Another major component of the CSPG family, phosphacan, is highly upregulated following different types of CNS injury in vivo (32)(33)(34).…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that cultured astrocytes produce neurocan and that the SW injury induced substantial upregulation of neurocan mRNA, which is consistent with previous in vitro (30) and in vivo (6,29,31) observations. Another major component of the CSPG family, phosphacan, is highly upregulated following different types of CNS injury in vivo (32)(33)(34).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, NG2 immunoreactivity was associated with blood vessels in the lesion core. Other studies have similarly demonstrated the presence of CSPGs at sites of CNS injury, including NG2 (Levine, 1994), neurocan (McKeon and Buck, 1997), phosphacan (Barker et al, 1996), versican McKeon et al, 1999) and brevican (Jaworski et al, 1995;Haas et al, 1999;Thon et al, 2000). In vitro, and at sites of CNS injury, CSPGs are generally produced by reactive glia: astrocytes are thought to make neurocan and phosphacan while oligodendrocyte precursors make NG2, neurocan, and phosphacan (Maurel et al, 1994;Faissner et al, 1994;Engel et al, 1996;Meyer-Pullitz et al, 1996;Nishiyama et al, 1999;Asher et al, 2000a).…”
Section: Chondroitin Sulphate Proteoglycansmentioning
confidence: 86%
“…Astrocytes form the bulk of the mature glial scar, responding to injuries by changing their cellular phenotype and behaviour (for review see Ridet et al, 1997). Astrocytes divide and/or migrate to the lesioned area, hypertrophy, up-regulate intermediate filament proteins glial fibrillary acidic protein (GFAP) and vimentin, and up-regulate a number of cellsurface and extracellular matrix (ECM) molecules, including proteoglycans (McKeon et al, 1991(McKeon et al, , 1995Haas et al, 1999;Asher et al, 2000). These changes develop over about 10 days leading to the classic appearance of the glial scar, which eventually consists of highly branched astrocytic processes attached to one another by junctional complexes, with plentiful ECM.…”
mentioning
confidence: 99%
“…Snow et al, 1990;McKeon et al, 1991McKeon et al, , 1995Dou and Levine, 1994;Smith-Thomas et al, 1994Fidler et al, 1999;Niederö st et al, 1999;Moon et al, 2001;Bradbury et al, 2002;Chen et al, 2002;Ughrin et al, 2003). Some inhibitory CS-PGs are expressed by astrocytes, including brevican (Yamada et al, 1997), neurocan (Friedlander et al, 1994;Haas et al, 1999;Asher et al, 2000) and phosphacan (McKeon et al, 1999). However, some CS-PGs that are up-regulated in the damaged CNS are produced by OPs, these include NG2 (Fidler et al, 1999) and versican .…”
mentioning
confidence: 99%